Comparison of the Use of Indonesian, Foreign Languages and Regional Languages in Naming Places in the Mataram Region - Wahyuni, Wika; Sudika, I Nyoman; Ramdantia, Baiq Alvi; Nazir, Yuniar Nuri (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research was motivated by the emergence of various names of places in the Mataram city area with names in foreign languages. On the one hand, the use of foreign languages aims to make it easier for foreign immigrants to understand places in Indonesia, but on the other hand, the use of foreign languages in the public sphere, in the form of advertising and promotion of goods and services, is under the pull of globalization/internationalization interests. Prestige or a sense of pride in using a foreign language is an interesting aspect to study further. This research aims to record the use of language in naming tourist and culinary attractions in the city of Mataram and see the dominance of language. Data was collected using the documentation method, then the data was analyzed using the content analysis method which includes data reduction, data presentation and drawing conclusions. Data is presented in the form of tables, diagrams and narrative text. Based on the results of the analysis, two linguistic features were found in naming places, namely monolingual and bilingual. The monolingual feature is divided into 57 foreign languages, 47 Indonesian languages, and 9 regional languages. Meanwhile, the form of the bilingual feature is divided into two, namely a combination of foreign languages and regional languages with 13 data and a combination of foreign language and Indonesian with 3 data.